Enhanced Photocatalytic Fuel Denitrification over TiO2/α-Fe2O3 Nanocomposites under Visible Light Irradiation - Huang, Renkun; Liang, Ruowen; Fan, Haimei; Ying, Shaoming; Wu, Ling; Wang, Xuxu; Yan, Guiyang (Scientific reports, 2017)
With increasingly stringent environmental regulations, the removal of nitrogen-containing compounds (NCCs) from gasoline fuel has become a more and more important research subject. In this work, we have successfully synthesized TiO 2 /α-Fe 2 O 3 heterogeneous photocatalysts with different mass ratios of TiO 2 vs . α-Fe 2 O 3 . Taking photocatalytic denitrification of typical alkali NCCs, pyridine, in gasoline fuel under visible light irradiation (λ ≥ 420 nm) as the model reaction, the TiO 2 /α-Fe 2 O 3 hybrids have exhibited enhanced photocatalytic activity compared with pure TiO 2 and α-Fe 2 O 3 , giving a pyridine removal ratio of ∼100% after irradiation for 240 min. The improved photocatalytic performance can be attributed to the integrative effect of the enhanced light absorption intensity and more efficient separation of photogenerated electron-hole pairs. Importantly, this type of heterogeneous photocatalysts can be easily separate in the reaction medium by an external magnetic field that is very important for industrial purpose. In addition, major reaction intermediates have been identified by the liquid chromatograph-mass spectrometer (HPLC-MS) and a tentative photocatalytic denitrification mechanism has been proposed.